Pigs make me sneeze! - Willems, Mo. (New York : Hyperion Books for Children, 2009)
Could Elephant be allergic to Piggy? Oh no, will they ever be able to see each other again?
Keywords: Swine -- Juvenile fiction; Elephants -- Juvenile fiction; Friendship -- Juvenile fiction